Risk management and ESG disclosure: Trends, gaps, and emerging themes – A bibliometric exploration - Wan Abdullah, Wan Razazila; Zamri, Norhayati; Mohd Fatzel, Farah Husna; Ab Rahman, Liyana; Puteh Salin, Ahmad Saiful Azlin (International Journal of Accounting, Finance and Business, 2026)
This study conducts a bibliometric meta-analysis to map the intellectual structure and research evolution at the intersection of risk management (RM) and environmental, social, and governance (ESG) practices. Drawing on 1,275 Scopus-indexed publications from 2009 to 2025, the dataset includes 47,812 citations, an h-index of 102, and contributions from over 3,800 authors across 71 countries. Data cleaning and harmonization were performed using OpenRefine and biblioMagika®, while VOSviewer enabled science mapping through co-authorship, keyword co-occurrence, and bibliographic coupling. The analysis identifies four thematic clusters: (1) ESG risk disclosure and financial performance, (2) governance and regulatory frameworks, (3) climate and sustainability risk integration, and (4) risk-based ESG investment strategies. Emerging themes include transition risk modeling, ESG stress testing, and digital ESG analytics. Publication trends show sharp growth after 2015, driven by regulatory reforms and investor demand for ESG-aligned practices. Geospatial analysis highlights dominant contributions from the United States, United Kingdom, China, and the European Union, alongside increasing engagement from Southeast Asia and Latin America. Co-authorship mapping reveals moderately dense collaboration with influential hubs and cross-disciplinary linkages. Overall, the study provides a comprehensive synthesis of RM–ESG research, offering insights for academics, policymakers, and institutional stakeholders advancing sustainable risk governance.